Modulation of brain activity and tremor severity by NeuroEpo in Parkinson’s patients with varying tremor amplitudes - Jiman, Ahmad A.; Attar, Eyad Talal (Frontiers in Neurology, 2025)
BackgroundTremors, particularly those related to Parkinson’s disease (PD), significantly affect quality of life. In this study, we inspected the effects of NeuroEpo versus placebo on brain function and tremor inhibition in patients with high-amplitude tremors (HAT) and low-amplitude tremors (LAT).ObjectivesTo assess the efficacy of NeuroEpo in enhancing coherence and power spectral density (PSD) relative to tremor severity, and to explore differences in stimulation parameters and medication requirements between patients with HAT and LAT.MethodsA double-blind randomized controlled trial was conducted on 16 participants diagnosed with PD. Participants were stratified into the HAT (n = 8) and LAT (n = 8) groups. Deep brain stimulation (DBS) parameters were individualized, and participants received either NeuroEpo or a placebo. The study was approved by the IRP on October 2, 2001, and all research participants gave informed consent. This research was conducted at the University of Quebec at Montreal, McGill University in Montreal, Quebec, Canada, and CHU de Bordeaux at Hôpital du Haut-Lévêque, Pessac, France. Data were obtained from authentic online platforms using DOI-referenced sources. Outcome measures included tremor severity, brain activity via EEG, and medication dosage.ResultsNeuroEpo treatment produced a significant increase in coherence and PSD, particularly in the 20–21 Hz frequency band, compared with placebo. Patients with LAT required higher stimulation intensities and medication doses than those with HAT, suggesting a more complex disease profile. The combination of NeuroEpo and DBS resulted in improved both motor and cognitive functions. A two-way ANOVA indicated a significant main effect of treatment (p < 0.05), with the NeuroEpo group exhibiting a significantly greater PSD than the placebo group.ConclusionNeuroEpo may provide an adjuvant therapeutic aid for the control of tremor and improvement in brain function in PD patients. Customized treatment approaches incorporating tremor amplitude may improve therapeutic benefit and patient well-being. Future research should follow up on the long-term psychosocial effects of combined interventions.